Novel Arsenic Nanoparticles Are More Effective and Less Toxic than As (III) to Inhibit Extracellular and Intracellular Proliferation of Leishmania donovani - Sudipta Chakraborty; Kaushik Bhar; Sandip Saha; Rajarshi Chakrabarti; Anjali Pal; Anirban Siddhanta (Journal of Parasitology Research)
Visceral leishmaniasis, a vector-borne tropical disease that is threatening about 350 million people worldwide, is caused by the protozoan parasite Leishmania donovani. Metalloids like arsenic and antimony have been used to treat diseases like leishmaniasis caused by the kinetoplastid parasites. Arsenic (III) at a relatively higher concentration (30 μg/mL) has been shown to have antileishmanial activity, but this concentration is reported to be toxic in several experimental mammalian systems. Nanosized metal (0) particles have been shown to be more effective than their higher oxidation state forms. There is no information so far regarding arsenic nanoparticles (As-NPs) as an antileishmanial agent. We have tested the antileishmanial properties of the As-NPs, developed for the first time in our laboratory. As-NPs inhibited the in vitro growth, oxygen consumption, infectivity, and intramacrophage proliferation of L. donovani parasites at a concentration which is about several fold lower than that of As (III). Moreover, this antileishmanial activity has comparatively less cytotoxic effect on the mouse macrophage cell line. It is evident from our findings that As-NPs have more potential than As (III) to be used as an antileishmanial agent.